Social Forestry Programme and its Impact in Haryana - Malik, P. S. (Indian Forester, 1991)
The Haryana Social Forestry Project was launched wHh World Bank assistance In 1982-83 for a period of five years to establish 67000 hectares of plantations with financial outlay of Rs. 333.26 millions but later on extended upto 31.3.91 and it is likely to be further extended by one more year. The main obJectlvea were to provide fuel, fodder, fruit, grasses, small timber and to generate employment In rural areas. By the end of March 1991 plantations have been raised over an area of 1 ,03,683 hectares and an amount of Rs. 597.75 mlliions has been spent. During the course of implementation we have learnt lessons that people's participation must be ensured If Social Forestry Programmes are to succeed but people's partiCipation is difficult to be achieved unless they are first persuaded that they can obtain tangible benefits from the programme.